2016
DOI: 10.1002/bmb.20950
|View full text |Cite
|
Sign up to set email alerts
|

An undergraduate laboratory class using CRISPR/Cas9 technology to mutate drosophila genes

Abstract: CRISPR/Cas9 genome editing technology is used in the manipulation of genome sequences and gene expression. Due to the ease and rapidity with which genes can be mutated using CRISPR/Cas9, we sought to determine if a single-semester undergraduate class could be successfully taught, wherein students isolate mutants for specific genes using CRISPR/Cas9. Six students were each assigned a single Drosophila gene, for which no mutants currently exist. Each student designed and created plasmids to encode single guide R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…In some cases, these experiences can be used to generate both laboratory reagents and data as well as data pertaining to student outcomes resulting from the implementation of CUREs. [21][22][23][24][25][26] Given student interest and the increased need to communicate cutting-edge research to undergraduate students, colleges and universities have begun instituting CRISPR-Casrelated CUREs with great success. Part of the reason why CUREs and other forms of course-based research that utilize CRISPR-Cas technologies are successful is due to the current curricula in molecular biology-based laboratory courses at diverse academic institutions, particularly fouryear colleges and universities.…”
Section: Course-based Undergraduate Research Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, these experiences can be used to generate both laboratory reagents and data as well as data pertaining to student outcomes resulting from the implementation of CUREs. [21][22][23][24][25][26] Given student interest and the increased need to communicate cutting-edge research to undergraduate students, colleges and universities have begun instituting CRISPR-Casrelated CUREs with great success. Part of the reason why CUREs and other forms of course-based research that utilize CRISPR-Cas technologies are successful is due to the current curricula in molecular biology-based laboratory courses at diverse academic institutions, particularly fouryear colleges and universities.…”
Section: Course-based Undergraduate Research Experiencesmentioning
confidence: 99%
“…Although data collection on the outcomes of CRISPR-Cas-based CUREs is ongoing, instructors report increased student learning and engagement after implementing CRISPR-Cas-based CUREs using various metrics. [21][22][23][24][25][26] Academic institutions have only recently started using CRISPR-Cas-based CUREs in their coursework; with increased interest in CRISPR-Cas-based CUREs, more rigorous studies on student achievement will undoubtedly help inform future activities at more institutions.…”
Section: Measuring Successmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Adame et al (2016) demonstrated that Drosophila Act79B null mutants appeared to jump normally, despite lacking the predominant actin found in the jump muscle (also called the tergal depressor of the trochanter, TDT). However, the sample size was small; therefore, in this study we investigated further the role of Act78B and other actin isoforms in the jump muscle of Drosophila.…”
Section: Introductionmentioning
confidence: 99%